2016
DOI: 10.1002/bjs.9964
|View full text |Cite
|
Sign up to set email alerts
|

Prospective nationwide outcome audit of surgery for suspected acute appendicitis

Abstract: Management of acute appendicitis in the Netherlands is preferably performed laparoscopically, characterized by a low conversion rate. Fewer superficial surgical-site infections occurred with laparoscopy, although the rate of abscess formation was no different from that following open surgery. A low normal appendix rate is the presumed effect of a mandatory preoperative imaging strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 19 publications
7
77
3
Order By: Relevance
“…In our study, only one patient had laparoscopic appendectomy. The perforation rate on histology 12 was 16.8% and this is comparable to report but higher than 6 the report published in the literature and in that study, 2,13 perforation was found in 11.0%. Reports have shown higher 14 rate of perforation.…”
Section: Morbidity and Mortality Most Common Complication Was Surgicasupporting
confidence: 80%
See 1 more Smart Citation
“…In our study, only one patient had laparoscopic appendectomy. The perforation rate on histology 12 was 16.8% and this is comparable to report but higher than 6 the report published in the literature and in that study, 2,13 perforation was found in 11.0%. Reports have shown higher 14 rate of perforation.…”
Section: Morbidity and Mortality Most Common Complication Was Surgicasupporting
confidence: 80%
“…SSI was the most common complication seen in 12.6% of patients 15 2 comparable to the report and lower than the report . The median length of the hospital stay was 8 days and this is higher 6 than the report . For the 17 patients who developed Superficial SSI, median length of hospital stay was 10 days and for the 4 patients who developed deep SSI, the median length of hospital stay was 12.5 days.…”
Section: Morbidity and Mortality Most Common Complication Was Surgicacontrasting
confidence: 64%
“…ultrasound, CT or MRI) in cases of suspected appendicitis has significantly reduced the incidence of a normal appearing appendix encountered during surgery [136]. Macroscopic distinction between a normal appendix and appendicitis during surgery can be difficult [137, 138].…”
Section: Intra-operative Proceduresmentioning
confidence: 99%
“…Surgical treatment of acute cholecystitis or appendicitis, is known to be associated with a higher risk of late abscess formation, due to retained stones in the abdominal cavity/wall or contamination of the wound at the time of surgery, respectively[5,6]. The differential diagnosis of a non-healing sinus includes tuberculosis, malignancy, presence of foreign bodies and communication with abdominal organs to the skin surface.…”
Section: Discussionmentioning
confidence: 99%